Baba Yaga : the wild witch of the East in Russian fairy tales - Forrester, Sibelan E. S. (Sibelan Elizabeth S.); Forrester, Sibelan E. S. (Sibelan Elizabeth S.); Goscilo, Helena, 1945-; Skoro, Martin (University Press of Mississippi, 2013)
Collection of twenty-nine fairy tales featuring Baba Yaga that draws from the famous collection of Aleksandr Afanas'ev, but also includes some tales from the lesser-known nineteenth-century collection of Ivan Khudiakov, along with images that show how artists have imagined her for over more than two centuries.